RUSSIA AND IRAN: TTEMPTS TO IMPLEMENT EW STRATEGIC STEPS IN THE CASPIAN-CENTRAL ASIAN OIL AND GAS INDUSTRY - MAKHMUDOV, Rustam (CENTRAL ASIA AND THE CAUCASUS, 2008)
The events of 2008 on the Caspian Basin and Central Asian natural gas and oil market clearly show that the key regional and world geopolitical players are looking for new ways to take the strategic initiative in the rivalry for access to the production, transportation, and purchase of crude oil and gas. Russia and Iran in particular have made several original proposals and taken specific measures aimed at raising competition in the region’s energy sector to an essentially higher level. It is worth taking a closer look at this. By the end of last year, the situation on the Central Asian natural gas market was developing quite dynamically. This was prompted by the appointment of a new president, G. Berdymukhamme-dov, in Ashghabad, who immediately demonstrated his desire to draw Turkmenistan out of its foreign policy lethargy. A traditional tool of national policy has been to stimulate contacts with foreign players regarding the laying of major pipelines in every possible direction and the sale of raw gas. In particular, Ashghabad initiated numerous ties with European and American diplomats with respect to the implementation of the pro-Western Trans-Caspian gas pipeline. G. Berdymukhammedov also con-firmed the agreement between Beijing and former president Niyazov on the laying of the Turkmenistan-China route. This of course aroused Moscow’s concern since it boded a significant weakening of its dominant position in the transit and purchase of natural gas from Turkmenistan. The Kremlin immediately took a preventive step against the Trans-Caspian route. In May 2007, Russia decided it was time to reconsider the agreement draft on building the Trans-Caspian gas pipeline, which was signed in December of the same year. This route was designed to pump 20 bcm of gas a year and is scheduled to go into operation no later than 2010.